Hetero‐Diels–Alder Cycloaddition with RAFT Polymers as Bioconjugation Platform. Issue 45 (2nd September 2020) - Beloqui, Ana; Mane, Shivshankar R.; Langer, Marcel; Glassner, Mathias; Bauer, Dennis M.; Fruk, Ljiljana; Barner‐Kowollik, Christopher; Delaittre, Guillaume
Abstract: We introduce the bioconjugation of polymers synthesized by RAFT polymerization, bearing no specific functional end group, by means of hetero‐Diels–Alder cycloaddition through their inherent terminal thiocarbonylthio moiety with a diene‐modified model protein. Quantitative conjugation occurs over the course of a few hours, at ambient temperature and neutral pH, and in the absence of any catalyst. Our technology platform affords thermoresponsive bioconjugates, whose aggregation is solely controlled by the polymer chains. Abstract : Already there: Polymers obtained by RAFT polymerization with thiocarbonylthio transfer agents possessing an electron‐deficient carbon–sulfur double bond undergo bioconjugation by hetero‐Diels–Alder cycloaddition, without the need for other reactive end groups. This ligation occurs over a few hours, at ambient temperature and near‐neutral pH, without any catalyst required.